Soroepidemiologia de Sarcocystis neurona, Toxoplasma gondii e Neospora spp. em cavalos Mangalarga Marchador criados no sul de Minas, Brasil - Ribeiro, Manoel Junqueira Maciel (2015)
The study subjects were the equine protozoal myeloencephalitis (MPE), caused by Sarcocystis neurona, toxoplasmosis, zoonosis caused by Toxoplasma gondii, and neosporosis, caused by Neospora caninum and N. hughesi. These protozoa are acquired by ingesting contaminated food and water, causing neurological and reproductive disorders, predominantly subclinical infections, causing losses to farmers. Once the southern Minas stands out in national equidculture for being the birthplace of Mangalarga Marchador horse, being economically strategic for the creation of the breed, the study aimed to determine the prevalence of antibodies against these parasites in horses of this breed created in the region and check the risk factors associated with positivity. 506 clinically healthy horses were analyzed, from 53 properties located in southern Minas Gerais. Serum samples were subjected to indirect immunofluorescence assay (IFA) with cutoff of 1:80, 1:64 and 1:50 respectively for S. neurona, T. gondii and Neospora spp. The seroprevalence found among horses for these three parasites were respectively 26%, 19.9% and 23.9%. In the properties, these prevalences were 88.3%, 71.6% and 85%. These results indicate that the southern Minas is an enzootic area for the three protozoa in Mangalarga Marchador horses, predominantly subclinical, chronic or asymptomatic infection. The horizontal transmission seems to be the main mode of transmission of these parasites and different risk factors are associated with seropositivity in horses. Further research is needed to establish which factors increase the risk of transmission of these agents, as well as determine which species of Neospora that infects horses.